The Last Clear Narrative - Zucker, Rachel (Book collections on Project MUSE., 2004)
Language is the rope and falling the perception, Zucker's poems are unsentimental, true to the disjunctive experiences of loving, giving birth, raising a child, being lonely, being alive. A poetry of the body, of desire, about human frailty and strength, The Last Clear Narrative fills a void in the history of women writing about everyday experience and speaks to the nature of narrative itself. Book jacket.